Natural characterization of the low course of the Camaquã River in Cristal city-RS - Beier, Elissandro Voigt; Poleto, Cristiano; Ferreira, Maria Eugênia Moreira Costa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
A portion of the rural territory of the Cristal City-RS was analyzed in order to assess the natural characteristics such as pedology, geology, geomorphology, water network, climatology and the biogeography of this geographical area. For the survey, bibliographical sources such as topographic charts, survey maps of IBGE, reference sources like phytogeographic surveys, and detailed studies of sedimentary and hydrological dynamics that transformed the region in the past were considered. From this study, specific characteristics for each of the analysis categories were mapped in definite charts and analyzed in their context of occurrence. As a result, it was possible to characterizate the natural conditions of the region whose current scenario presents significant differentiation by the anthropic interference in the environment.